Green Procurement in Construction: Analysis of the Readiness Level and Key Catalyst among Construction Enablers - Razali, Nurazri; Khalil, Natasha; Mohamad Bohari, Asmah Alia; Husin, Husrul Nizam (International Journal of Sustainable Construction Engineering and Technology, 2021)
In the concern of sustainability and increasing awareness of environmental degradation, the Malaysian government has promoted numerous initiatives on green growth and green procurement (GP) to maintain and minimize the ecological effects in construction. However, this initiative is still in the infancy stage as to date, there is no specific guideline delineated to the construction industry, and it has yet to be enforced by the government to the construction practitioners. In construction, green procurement is a new area, and immediate actions are needed upon the principles, guidelines, and policy and implementation framework. Hence, this research aims to analyse the readiness level, barriers, and key catalysts among construction enablers towards adopting green procurement in the construction industry. Questionnaires were distributed to 102 construction enablers, focusing on quantity surveying firms in the Klang Valley area (Kuala Lumpur and Selangor), and 87 returned the responses. The analysis uses descriptive statistics via mean score, and the standard deviation was used to measure the variables and the mean's dispersion. It is revealed that the consultants are ready to adopt green procurement. However, GP's implementation's top challenges are lack of internal expertise, low awareness about green procurement, and lack of established best practices, standardized procedures and guidelines. It can be summarized that promoting GP and its implementation requires government support in policies, initiatives, and incentives. As the current practice is fragmented, ideally, GP's adoption in construction projects needs to conform to the acceptable standards that enable specific provisions to acquire eco-friendly sustainable construction.